Digital Leadership and IT Strategy Execution in Emerging Economies - Angellia, Filda (Indonesian Scientific Publication, 2024)
Digital transformation has emerged as a critical driver for organizational success in today’s rapidly evolving technological landscape. This narrative review aims to explore how IT strategy is formulated and implemented in digital enterprises, particularly within developing countries. Using a systematic literature search across Scopus, IEEE Xplore, and Google Scholar, studies were selected based on thematic relevance, quality, and citation impact. Keywords included